Optimizing Arabic Vocabulary Mastery through Word Wall Media in the Firtalia Group at TMI Al-Amien Prenduan - Namlul Wadi; Munirul Abidin; Fatimah Azzahra (Jurnal Ilmiah Literasi Indonesia, 2026)
The fundamental problem faced by members of the "Firtalia" language interest group at TMI Al-Amien Prenduan is the low retention of vocabulary (mufradat) memorization, which negatively impacts their active communication skills. This study aims to enhance vocabulary mastery through the implementation of visual word wall media. The method employed is Classroom Action Research (CAR) conducted in four cycles, comprising planning, action, observation, and reflection. The subjects were 24 new members of the Firtalia group. Data collection instruments included participatory observation, interviews, written/oral tests, and documentation. Success indicators were set at an individual score of ≥ 65 and classical completeness of 75%. The results demonstrated a significant upward trend: in the pre-cycle, classical completeness was only 29.1% (average score 60). Following the intervention, there was a gradual increase in Cycle I (58.3%), Cycle II (79.1%), peaking in Cycles III and IV with stable completeness at 95.8% (average score 81.5). This study concludes that integrating word wall media effectively shifts the paradigm of vocabulary memorization from a cognitive burden to an interactive and enjoyable visual activity..